The Influence of Parental Parenting Styles, Teacher Creativity, and Peers on Student Interest in Learning at MA TANADA Waru Sidoarjo - Amalia Salsabilla; mufaizah; Masfufah (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research aims to determine how parenting styles, teacher creativity, and peers influence student learning interest at MA TANADA Waru Sidoarjo. This study uses a quantitative approach with a survey method. Data collection techniques were conducted through interviews, observations, questionnaires, and documentation. This study involved all MA TANADA Waru Sidoarjo, with 36 samples selected using total sampling technique. This study used a questionnaire with an eight-point Likert scale that was distributed via Google Form. The collected data were analyzed using the IBM SPSS version 26. This research emphasizes the importance of the role of creative teachers and peers in fostering students' interest in learning at home. The results show that the variables of teacher creativity and peers have a positive and significant influence on students' interest in learning. Conversely, the variable of parental care also has no significant effect.